2009
DOI: 10.3844/ojbsci.2009.36.39
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Human Herpesvirus Type 8 Infection in Cardiopathic Patients

Abstract: Problem statement: The possible contribution of viruses to vascular pathology is still a\ud controversial issue. Human herpesvirus type 8 (HHV-8) has been suggested to participate to the\ud pathogenetic events associated with atherosclerotic lesion establishment and progression. Recently, a\ud high incidence of infection of HHV-8 (11%) has been verified in the island of Sardinia. The aim of this\ud study was to evaluate a possible relationship between the HHV-8 infection and cardiovascular diseases in\ud the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Total RNA was extracted with a pureLink RNA Mini kit (Life Technologies, UK) and treated with TURBO DNase (Applied Biosystems, UK) before the synthesis of cDNA with a Super Script VILO kit (Invitrogen, Life Technologies, UK). RT-PCR amplification was performed using 200 ng of total RNA extracted from the infected cells as previously indicated [ 23 - 25 ]. Primers and conditions for RT-PCR amplification were as follows: orf26 took place with primers orf26 fw 5′-GCCGAAAGGATTCCACCATTGTGCT-3′ and orf26 rev 5′- GGGCCCCGGCCGATATTTTGG-3′ for 40 cycles (15'' at 95°C, 1' at 60°C and 15'' at 72°C) plus 10' at 72°C of extension; orf50 amplification took place with primers orf50 fw 5′-CATGCAGCGGGGTGAGCCTG-3′ and orf50 rev 5′- AGCAGCCCGGCGGTATCGTA-3′ for 40 cycles (15'' at 95°C, 1′ at 60°C and 15′ at 72°C); orf73 amplification took place with primers orf73 fw 5′- ATCCTCGGGAAATCTGGTCT-3′ and orf73 rev 5′-TTCAGCGTTTCAGTGTCTGC-3′ for 40 cycles (15'' at 95°C, 1′ at 60°C and 15′ at 72°C) plus 10′ at 72°C of extension.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted with a pureLink RNA Mini kit (Life Technologies, UK) and treated with TURBO DNase (Applied Biosystems, UK) before the synthesis of cDNA with a Super Script VILO kit (Invitrogen, Life Technologies, UK). RT-PCR amplification was performed using 200 ng of total RNA extracted from the infected cells as previously indicated [ 23 - 25 ]. Primers and conditions for RT-PCR amplification were as follows: orf26 took place with primers orf26 fw 5′-GCCGAAAGGATTCCACCATTGTGCT-3′ and orf26 rev 5′- GGGCCCCGGCCGATATTTTGG-3′ for 40 cycles (15'' at 95°C, 1' at 60°C and 15'' at 72°C) plus 10' at 72°C of extension; orf50 amplification took place with primers orf50 fw 5′-CATGCAGCGGGGTGAGCCTG-3′ and orf50 rev 5′- AGCAGCCCGGCGGTATCGTA-3′ for 40 cycles (15'' at 95°C, 1′ at 60°C and 15′ at 72°C); orf73 amplification took place with primers orf73 fw 5′- ATCCTCGGGAAATCTGGTCT-3′ and orf73 rev 5′-TTCAGCGTTTCAGTGTCTGC-3′ for 40 cycles (15'' at 95°C, 1′ at 60°C and 15′ at 72°C) plus 10′ at 72°C of extension.…”
Section: Methodsmentioning
confidence: 99%
“…The findings that HHV8 latency is characterized by persistent modifications in endothelial cell metabolism have led some authors to hypothesize a possible involvement of HHV8 infection in the development of a diffused chronic human disease such as DMT2 [65,75,[78][79][80][81][82]. Although KS is considered a rare disease, HHV8 infection has been found to have a high prevalence in some countries, namely in the Mediterranean and African regions [81][82][83]. Ingianni et al [81] were the first authors to demonstrate a strong epidemiological correlation between HHV8-infection and DMT2 patients in a Southern Italian region.…”
Section: Hhv8 Prevalence In Chronic Diseasesmentioning
confidence: 99%
“…Several studies have demonstrated that HHV8 infection induces intense and long-lasting alterations in the physiology of infected cells [3][4][5]. HHV8 has also been associated to widely diffused chronic diseases [6][7][8][9][10][11][12], such as cardiovascular disease and diabetes mellitus type 2 (DM2). HHV8 induces a permanent inflammatory condition with impairment of B-lymphocyte activity and alteration in the function of NK-cells [13,14], as also found in DM2 patients.…”
Section: Introductionmentioning
confidence: 99%